Wild ducks flying backward : the short writings of Tom Robbins. - Robbins, Tom, 1932- (Bantam Books, 2005)
A generous sampling, collected here for the first time and including works as diverse as scholarly art criticism and some decidedly untypical country-music lyrics. Embedded in this primarily journalistic compilation are a couple of short stories, a sheaf of largely unpublished poems, and an off-beat assessment of our divided nation.